Development of water-in-oil emulsions as delivery vehicles and testing with a natural antimicrobial extract - Colucci, Giovana (2018)
Water-in-oil (W/O) emulsions have high potential for several industrial areas as delivery systems of hydrophilic compounds. In general, they are less studied than oil-in-water (O/W) systems, namely in what concerns the so-called fluid systems, partly due to problems of instability. In this context, this work aimed to produce stable W/O emulsions from a natural oil, sweet almond oil, to be further tested as vehicles of natural hydrophilic extracts, here exemplified with an aqueous cinnamon extract. Firstly, a baseW/O emulsion using a high-water content (40/60, v/v) was developed by testing di erent mixtures of emulsifiers, namely Tween 80 combined with Span 80 or Span 85 at di erent contents. Among the tested systems, the one using a 54/46 (v/v) Span 80/Tween 80 mixture, and subjected to 12 high-pressure homogenizer (HPH) cycles, revealed to be stable up to 6 months, being chosen for the subsequent functionalization tests with cinnamon extract (1.25–5%; w/v; water-basis). The presence of cinnamon extract leaded to changes in the microstructure as well as in the stability. The antimicrobial and antioxidant analysis were evidenced, and a sustained behavior compatible with an extract distribution within the two phases, oil and water, in particular for the higher extract concentration, was observed.